Caracterização eletroquímica do eletrólito sólido NASICON Li1,5Al0,5Ge1,5(PO4)3 (LAGP) - Zallocco, Vinicius Martins (Universidade Federal de São Carlos, 2021)
Solutions to the environmental and social challenges of postmodern society converge on a common point: sustainability. Doing more with less and using environmentally friendly materials is imperative. Energy storage is critical to today's society. Some state-of-the-art limits for the current lithium-ion batteries need to be overcome in this scenario, including greater operational safety. Many research groups study several alternatives. Thus, this work aims to contribute to the development of improved solid-state batteries. Among the plentiful factors that contribute to the correct functioning of a battery, the electrochemical stability window of the electrolyte is one of them. In solid electrolytes, in general, this electrochemical stability window is overestimated due to the slow solid-state reaction kinetics. In fact, methods employing computer simulation have shown that the electrochemical stability of some solid electrolytes is lower than that estimated by experimental methods. Thus, the present work proposes studying the electrochemical stability window of the solid electrolyte NASICON Li1,5Al0,5Ge1,5(PO4)3 (LAGP) through cyclic voltammetry with three different cell configurations, one of which would be capable of detecting the real electrochemical stability window of solid electrolytes.
Electrochemical stability window of NASICON solid-state electrolyte lithium aluminum germanium phosphate (LAGP)
Keywords: Bateria de estado sólido; Janela eletroquímica; Voltametria cíclica; Reação de estado sólido; Solid state battery; Electrochemical window; Cyclic voltammetry; Solid-state reaction; NASICON; LAGP; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS